2016
DOI: 10.1152/ajpgi.00087.2016
|View full text |Cite
|
Sign up to set email alerts
|

Night workers with circadian misalignment are susceptible to alcohol-induced intestinal hyperpermeability with social drinking

Abstract: Alcohol-induced intestinal hyperpermeability (AIHP) is a known risk factor for alcoholic liver disease (ALD), but only 20-30% of heavy alcoholics develop AIHP and ALD. The hypothesis of this study is that circadian misalignment would promote AIHP. We studied two groups of healthy subjects on a stable work schedule for 3 mo [day workers (DW) and night workers (NW)]. Subjects underwent two circadian phase assessments with sugar challenge to access intestinal permeability between which they drank 0.5 g/kg alcohol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
56
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(59 citation statements)
references
References 52 publications
2
56
0
1
Order By: Relevance
“…In a following week, all subjects were given red wine (0.5 g of ethanol per kg body weight) every day after finishing work and before bedtime for 1 week . Blood samples were collected with same procedures to baseline samples (postalcohol samples) . This study has demonstrated that nighttime workers but not daytime workers have delayed melatonin secretion peak after 1 week alcohol period, and alcohol consumption increases gut permeability only in nighttime workers, suggesting that nighttime workers are more susceptible for alcohol drinking than daytime workers .…”
Section: Functional Roles and Therapeutic Potentials Of Melatonin Andmentioning
confidence: 99%
See 2 more Smart Citations
“…In a following week, all subjects were given red wine (0.5 g of ethanol per kg body weight) every day after finishing work and before bedtime for 1 week . Blood samples were collected with same procedures to baseline samples (postalcohol samples) . This study has demonstrated that nighttime workers but not daytime workers have delayed melatonin secretion peak after 1 week alcohol period, and alcohol consumption increases gut permeability only in nighttime workers, suggesting that nighttime workers are more susceptible for alcohol drinking than daytime workers .…”
Section: Functional Roles and Therapeutic Potentials Of Melatonin Andmentioning
confidence: 99%
“…A previous study has analyzed the effects of moderate alcohol drinking on circadian rhythms using 11 daytime workers and 11 nighttime workers. In this study, all subjects were told to avoid alcohol drinking and have usual sleep schedule for 1 week . After an alcohol‐free week, subjects were kept in dim light, blood samples were collected, and serum melatonin levels were analyzed in every hour for 24 hours (baseline samples) .…”
Section: Functional Roles and Therapeutic Potentials Of Melatonin Andmentioning
confidence: 99%
See 1 more Smart Citation
“…This suggests that circadian disruption contributes to IHP and a pro-inflammatory state, due, at least in part, to perturbed relationships between intestinal microbiota and intestinal gene expression. Dr. Swanson presented a recent human study on the effects of circadian disruption on alcohol-induced IHP (AIHP) comparing night-shift to day-shift workers for response to small doses of alcohol (0.5g/kg=2 glasses of wine/day for 7 days) 9 . Night-workers had increased AIHP, which was correlated with 24-hour area under the curve (AUC) of serum melatonin, a measure of central circadian alignment.…”
Section: Circadian Dysrhythmia In Gi Diseasesmentioning
confidence: 99%
“…Further, transplantation of stool from patients with alcoholic hepatitis into alcohol-fed mice caused severe ASH compared to stool transplantation from control subjects (Llopis et al, 2016). Recent data from Keshavarian’s lab suggest that disruption of circadian rhythms promotes alcohol-induced dysbiosis and gut leakiness (Summa et al, 2013; Swanson et al, 2016; Voigt et al, 2014), and could therefore be a susceptibility factor for alcohol-induced, gut-derived inflammation. Disrupted circadian rhythms are common in western societies, affecting at least 30% of the population through shift work and social jet lag (Roenneberg, Allebrandt, Merrow, & Vetter, 2012; Zelinski, Deibel, & McDonald, 2014), which intriguingly correlates to that fact that 30% of alcoholics develop dysbiosis, gut leakiness, and clinically relevant organ damage (Gao & Bataller, 2011).…”
Section: Alcohol and Mucosal Inflammationmentioning
confidence: 99%